The Complexities of Cultural Identity in R. F Kuang's Babel, or the Necessity of Violence (2022) - Ning Salsabila Zahro (FAKULTAS ILMU BUDAYA, 2026)
This study examines the complexities of cultural identity in R. F. Kuang’s Babel, or the Necessity of Violence (2022) using Stuart Hall’s theory of cultural identity. The study aims to reveal how the novel constructs the complexities of cultural identity experienced by diasporic subjects in the novel and to examine the author’s critical position. This research uses qualitative descriptive method. The data are collected through close reading and analyzed using cultural identity theory. The findings show that the novel constructs the complexities of cultural identity through four interrelated themes, namely identity erasure, cultural adaptation and assimilation as a strategy for acceptance, the emotional impact of cultural adaptation, and resistance as the reclamation of identity. The study also finds that the novel criticizes British imperialism and colonialism by portraying language, education, and translation as tools that support imperial power and exploit colonized subjects.
Finalisasi Repository/HASYIM Agustus 2026
Keywords: Asian American literature; British imperialism; colonialism; cultural identity; diaspora; identity construction